Hypothyroidism and the Risk of Venous Thromboembolism: A Nationwide Cohort Study - Wei, Wei-Ting; Liu, Peter Pin-Sung; Lin, Shu-Man; Peng, Carol Chiung-Hui; Wang, Jen-Hung; Huang, Huei-Kai; Loh, Ching-Hui (Thrombosis and Haemostasis, 2020)
Background Previous studies have shown that hypothyroidism may have an impact on blood coagulation. However, how hypothyroidism and thyroxine replacement therapy (TRT) affect the risk of venous thromboembolism (VTE) remains controversial. This study aimed to examine the associations of hypothyroidism and TRT with VTE risks.Materials and Methods This nationwide population-based cohort study was conducted using Taiwan's National Health Insurance Research Database. We enrolled 10,818 hypothyroid patients (the exposed cohort) and 21,636 non-hypothyroid subjects (the unexposed cohort) between 2001 and 2014 after 1:2 exact matching according to age, sex, and index year. Hypothyroid patients were further divided into two groups depending on whether they received TRT or not. Adjusted hazard ratios (aHRs) for VTE were calculated using Fine and Gray competing risk models.Results The mean follow-up period was 7.5 years. Hypothyroidism was significantly associated with a higher risk of VTE (aHR = 1.83 [95% confidence interval [CI]: 1.44–2.33, p < 0.001]). Among hypothyroid patients, the TRT subgroup had a non-significant trend of lower VTE risk than the non-TRT subgroup (aHR = 0.73 [95% CI: 0.52–1.01, p = 0.058]). The analysis for individual events revealed a significant association between TRT use and a lower risk of pulmonary embolism among hypothyroid patients (aHR = 0.34 [95% CI: 0.13–0.88, p = 0.026]).Conclusion The data suggest that hypothyroidism was significantly associated with an increased risk of VTE. Among hypothyroid patients, a non-significant trend of lower VTE risk in patients treated with TRT was observed. Further prospective studies or clinical trials are necessary to confirm causality.
Keywords: hypothyroidism; venous thromboembolism; deep vein thrombosis; pulmonary embolism; thyroxine